Prototype Design of a Fishing Boat Safety Monitoring System Using LoRa and Microsensor Devices - Sugiarto, Eka; Suhendi, Asep; Abdussalam, M. Yusup; Husniah, Zahira Aulia; Lestari, Annisa Puji (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2023)
This paper reports a prototype of a low-cost tracking and monitoring system to address the challenges faced by Indonesian fishermen. The lack of safety equipment in their boats exposes them to high risks of work-related accidents and illnesses. Data from the National Basarnas Center reveals a staggering 24,000 annual fatalities among fishermen during their activities. These issues stem from a combination of factors: poorly designed boats, low prioritization of safety, and the lack of readily available preventive measures. Moreover, the development of telecommunications infrastructure in aquatic areas presents its unique obstacles. In response, this study proposes a prototype design for a "Fishing Boat Safety Monitoring System" utilizing LoRa and Microsensors for proactive and preventive measurement by tracking the boat position and sending the data via a long-distance wireless transmission with Low-Power Wide Area Network (LPWAN) scheme based on frequency-spread spectrum technology. This LPWAN serves as the substitution for cellular network which is usually not available in the ocean. The tracking system uses a low-cost TTGO T-Beam LoRa32 V1.1 Microcontroller Unit (MCU) board that has an embedded SX1276 LoRa module and Neo-6M GPS module. The system also uses a GY-25 gyroscope microsensor. The system implemented a 923 MHz LoRa signal for point-to-point communication between the transmitter to receiver. This research has successfully yielded a developed device capable of tracking the location of boats up to 2 km from the shoreline with -113 dBm received signal strength indicator (RSSI) and around 60% of data quality of service (QoS). Further research will explore the use of high-gain antennas and signal amplifiers integration with embedded LoRa on the MCU board to expand the coverage area of the LoRa signal.